1933
DOI: 10.1021/ie50278a004
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopicity of Fertilizer Salts

Abstract: A previous paper (1) a study was made of the hygroscopicities of various fertilizer materials and of mixtures of these having common ions. The nitrogen fixation products-calcium nitrate and ammonium nitrate, as well as urea-were found among the most hygroscopic of fertilizer materials. The fertilizer salts with two elements available for plant food-potassium nitrate, monopotassium phosphate, and monoammonium phosphate-proved to be the least hygroscopic of soluble materials. The hygroscopicity of a mixture was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1934
1934
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
(2 reference statements)
0
12
0
1
Order By: Relevance
“…A rather complex laboratory apparatus was used by USDA investigators to measure the water vapor pressure above saturated solutions of pure fertilizer salts and salt pairs (51,53).…”
Section: Isoteniscope Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rather complex laboratory apparatus was used by USDA investigators to measure the water vapor pressure above saturated solutions of pure fertilizer salts and salt pairs (51,53).…”
Section: Isoteniscope Methodsmentioning
confidence: 99%
“…In preparing humidity-control solutions, a suitable salt or salt pair is first selected from published vapor pressure data (51,52,53). Procedure is generally the same as with the more sophisticated cabinet, except that time must be allowed for air-solution equilibrium to be reached, and door openings must be minimized to retain humidity.…”
mentioning
confidence: 99%
“…Comparative experiments were carried out with superphosphate and double superphosphate. (12) Glancy, Wright, and Oon, Ind. Eng.…”
Section: Mixturesmentioning
confidence: 99%
“…When superphosphate is mixed with ammonium sulfate, as is now common practice in the preparation of mixed fertilizers, reaction may take place between the ammonium sulfate and the monocalcium phosphate in the superphosphate: Ca(H2PO")2 + ( 4)28 4 = CaS04 + 2NH4H2P04 Merz and his co-workers (7) have shown that calcium sulfate and monoammonium phosphate are the stable pair of these reciprocal salt pairs. A mixture of monocalcium phosphate and ammonium sulfate containing an excess of the former will therefore react in the presence of moisture until the ammonium sulfate no longer exists in the solid phase.…”
Section: Calcium Phosphate Mixturesmentioning
confidence: 99%